The material effects and cultural heritage in the city of Bou Saada through the ages - dehmeche, souhila (The Algerian Historical Journal, 2026)
The objective of the study on the subject of the material heritage and cultural heritage of the city of Bou Saada is to shed light on the potential of heritage, civilization and history by introducing it and its material heritage, which has resulted from the human presence and the succession of civilizations. Its inhabitants have valuable architectural and historical facilities. The material heritage of a pre-historic period dates back to the modern era requires us to preserve, preserve and value its monuments. The importance of the study therefore lies in the fact that it is in addition to the definition of our history and heritage and that it is possible to make use of these infrastructures in order to promote the region and to restore the material cultural heritage that it possesses. One of the most important findings of the study is that the city of Bou Saada has a historic high standing because of the succession of human civilizations. The latter has had many tangible, tangible and tangible effects, as well as its cultural and social diversity and geographical location. This study has highlighted some of the factors that must be exploited and invested in the region ' s development and restoration of its leadership.